Violaceae endémicas del Perú - León, Blanca (2006)
The Violaceae are represented in Peru by 12 genera and 61 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), between herbs, shrubs and trees. Here we recognize 10 endemic species in three genera. Viola is the genus with more endemic species. The systematics of both the family and the genus Viola are currently under study, and taxonomic changes and novelties are expected. Endemic species are found mainly in Very Humid Montane Forests, Mesoandean and High-Andean regions, between 150 and 4600 m elevation. We applied IUCN categories and criteria to only one species. None of the endemic species have been recorded to date within Peru’s protected areas system.